A portrait of James Dean [videorecording (DVD)] : Joshua Tree, 1951 - Mishory, Matthew; Preston, James; Glenn, Dan; Rain, Dalilah; Singletary, Edward (Wolfe, 2013)
Set primarily in the early 1950s and focusing on James Dean's experiences as an up-and-coming actor in Los Angeles, the film is a series of revealing and sometimes dreamlike vignettes that blend biographical and fictionalized elements to present pivotal moments in a remarkable life.